2020
DOI: 10.1002/slct.202001970
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Fibrils Extracted from Bamboo Chips as a Reinforcing Material for Prolonged Drug Release

Abstract: Despite significant improvements in the intelligent delivery of drugs, the search for drug carriers with low cost and long‐term sustainable release still faces enormous challenges. In this study this issue was addressed for porous cellulose‐based aerogels by developing a Temperature/pH stimuli‐responsive carrier for drug controlled release. The prepared aerogels exhibited a smart 3D network with large specific surface area (112.6 m2 g−1) that facilitated the loading and transport of drug molecules. The aerogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The release performances were studied in function of pH and temperature. The best conditions found for the release process were neutral pH and 37 • C temperature, perfectly fitting with the physiologic conditions of the human body [81].…”
Section: Drug Releasementioning
confidence: 62%
“…The release performances were studied in function of pH and temperature. The best conditions found for the release process were neutral pH and 37 • C temperature, perfectly fitting with the physiologic conditions of the human body [81].…”
Section: Drug Releasementioning
confidence: 62%
“…Whereas other routes of administration seem to be safe for the use of nanocellulose particles. For example, an oral acute toxicity study showed that when porous cellulose‐based aerogels were synthesized from bamboo pulp, no toxicity was found in mice with concentrations up to 6400 mg/kg after oral administration 154 …”
Section: In Vivo Experiments Of Polymer Gelsmentioning
confidence: 99%